Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

Use of an airborne lidar system to model plant species composition and diversity of Mediterranean oak forests. - Simonson, William D; Allen, Harriet D; Coomes, David A (Conservation biology : the journal of the Society for Conservation Biology, 2012)
Airborne lidar is a remote-sensing tool of increasing importance in ecological and conservation research due to its ability to characterize three-dimensional vegetation structure. If different aspects of plant species diversity and composition can be related to vegetation structure, landscape-level assessments of plant communities may be possible. We examined this possibility for Mediterranean oak forests in southern Portugal, which are rich in biological diversity but also threatened. We compared data from a discrete, first-and-last return lidar data set collected for 31 plots of cork oak (Quercus suber) and Algerian oak (Quercus canariensis) forest with field data to test whether lidar can be used to predict the vertical structure of vegetation, diversity of plant species, and community type. Lidar- and field-measured structural data were significantly correlated (up to r= 0.85). Diversity of forest species was significantly associated with lidar-measured vegetation height (R(2) = 0.50, p < 0.001). Clustering and ordination of the species data pointed to the presence of 2 main forest classes that could be discriminated with an accuracy of 89% on the basis of lidar data. Lidar can be applied widely for mapping of habitat and assessments of habitat condition (e.g., in support of the European Species and Habitats Directive [92/43/EEC]). However, particular attention needs to be paid to issues of survey design: density of lidar points and geospatial accuracy of ground-truthing and its timing relative to acquisition of lidar data.
Keywords: Biodiversity; Biological; cluster analysis; Conservation of Natural Resources; Conservation of Natural Resources: methods; Ecosystem; mediterranean oak forest; Models; Portugal; predictive modeling; Quercus; Remote sensing; Remote Sensing Technology; Remote Sensing Technology: methods; Species Specificity; vascular plants

Plant neighbour identity matters to belowground interactions under controlled conditions. - Armas, Cristina; Pugnaire, Francisco Ignacio (PloS one, 2011)
Root competition is an almost ubiquitous feature of plant communities with profound effects on their structure and composition. Far beyond the traditional view that plants interact mainly through resource depletion (exploitation competition), roots are known to be able to interact with their environment using a large variety of mechanisms that may inhibit or enhance access of other roots to the resource or affect plant growth (contest interactions). However, an extensive analysis on how these contest root interactions may affect species interaction abilities is almost lacking.
The following values have no corresponding Zotero field: accession-num: 22114696
Keywords: biomass; citation; Ecosystem; Environment; Plant Development; Plant Roots; Plant Roots: growth & development; Species Specificity

Acorn crop size and pre-dispersal predation determine inter-specific differences in the recruitment of co-occurring oaks. - Espelta, Josep Maria; Cortes, P.; Molowny-Horas, R.; Retana, J. (Oecologia, 2009)
The contribution of pre-dispersal seed predation to inter-specific differences in recruitment remains elusive. In species with no resistance mechanisms, differences in pre-dispersal predation may arise from differences in seed abundance (plant satiation) or in the ability of seeds to survive insect infestation (seed satiation). This study aimed to analyse the impact of pre-dispersal acorn predation by weevils in two co-occurring Mediterranean oaks (Quercus ilex and Quercus humilis) and to compare its relevance with other processes involved in recruitment. We monitored the patterns of acorn production and acorn infestation by weevils and we conducted experimental tests of acorn germination after weevil infestation, post-dispersal predation and seedling establishment in mixed forests. Monitoring and experimental data were integrated in a simulation model to test for the effects of pre-dispersal predation in recruitment. In both oaks pre-dispersal acorn infestation decreased with increasing acorn crop size (plant satiation). This benefited Q. ilex which exhibited stronger masting behaviour than Q. humilis, with almost a single and outstanding reproductive event in 6 years. Acorn infestation was more than twice as high in Q. humilis (47.0%) as in Q. ilex (20.0%) irrespective of the number of seeds produced by each species. Although germination of infested acorns (seed satiation) was higher in Q. humilis (60%) than in Q. ilex (21%), this could barely mitigate the higher infestation rate in the former species, to reduce seed loss. Conversely to pre-dispersal predation, no inter-specific differences were observed either in post-dispersal predation or seedling establishment. Our results indicate that pre-dispersal predation may contribute to differences in seed supply, and ultimately in recruitment, between co-existing oaks. Moreover, they suggest that seed satiation can barely offset differences in seed infestation rates. This serves as a warning against overemphasising seed satiation as a mechanism to overcome seed predation by insects.
The following values have no corresponding Zotero field: accession-num: 19544074
Keywords: Animals; Feeding Behavior; Feeding Behavior: physiology; germination; Germination: physiology; Models, Biological; Quercus; Quercus: physiology; Seeds; Seeds: growth & development; Spain; Species Specificity; weevils; Weevils: physiology

Medicinal plants in the Mediterranean area: synthesis of the results of the project Rubia. - González-Tejero, M R; Casares-Porcel, M; Sánchez-Rojas, C P; Ramiro-Gutiérrez, J M; Molero-Mesa, J; Pieroni, A; Giusti, M E; Censorii, E; de Pasquale, C; Della, a; Paraskeva-Hadijchambi, D; Hadjichambis, a; et al. (Journal of ethnopharmacology, 2008)
Within the scope of the European project RUBIA (ICA3-2002-10023), research has been performed on the traditional use and handling of plant species in several Mediterranean countries, Albania, Algeria, Cyprus, Egypt, Italy, Morocco, and Spain. This paper synthesises the chief results related to the medicinal utilization of those plants.
Keywords: Ethnobotany; Medicinal; Medicinal plants; Mediterranean; Mediterranean Region; Plants; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T.; Marañón, Teodoro; Murillo, José M.; Schulin, Rainer; Robinson, Brett H. (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
The following values have no corresponding Zotero field: accession-num: 17602809
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T; Marañón, Teodoro; Murillo, José M; Schulin, Rainer; Robinson, Brett H (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

The influence of linear elements on plant species diversity of Mediterranean rural landscapes: assessment of different indices and statistical approaches. - García del Barrio, J M; Ortega, M; Vázquez De la Cueva, A; Elena-Rosselló, R (Environmental monitoring and assessment, 2006)
This paper mainly aims to study the linear element influence on the estimation of vascular plant species diversity in five Mediterranean landscapes modeled as land cover patch mosaics. These landscapes have several core habitats and a different set of linear elements--habitat edges or ecotones, roads or railways, rivers, streams and hedgerows on farm land--whose plant composition were examined. Secondly, it aims to check plant diversity estimation in Mediterranean landscapes using parametric and non-parametric procedures, with two indices: Species richness and Shannon index. Land cover types and landscape linear elements were identified from aerial photographs. Their spatial information was processed using GIS techniques. Field plots were selected using a stratified sampling design according to relieve and tree density of each habitat type. A 50x20 m2 multi-scale sampling plot was designed for the core habitats and across the main landscape linear elements. Richness and diversity of plant species were estimated by comparing the observed field data to ICE (Incidence-based Coverage Estimator) and ACE (Abundance-based Coverage Estimator) non-parametric estimators. The species density, percentage of unique species, and alpha diversity per plot were significantly higher (p < 0.05) in linear elements than in core habitats. ICE estimate of number of species was 32% higher than of ACE estimate, which did not differ significantly from the observed values. Accumulated species richness in core habitats together with linear elements, were significantly higher than those recorded only in the core habitats in all the landscapes. Conversely, Shannon diversity index did not show significant differences.
Keywords: Biodiversity; Conservation of Natural Resources; Conservation of Natural Resources: statistics & nu; core habitat; diversity; Ecosystem; ecotones; Environmental Monitoring; Environmental Monitoring: methods; Geography; landscape; linear elements; Mediterranean; Mediterranean Region; Plant Development; Poaceae; Poaceae: growth & development; Shannon index; Species richness; Species Specificity; Trees; Trees: growth & development